Policy Assignment Strategies with Somewhat Flexible Exchange Rates Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The choice of assigning monetary or fiscal policy to external balance is complicated when the authorities are concerned with both the current account balance and the exchange rate. A strategy of using monetary policy to control the current account via the exchange rate may fail, because the relative-price effect is likely to be offset by the effect of monetary policy on aggregate demand. An alternative strategy, in which fiscal policy is assigned to limit shifts in the current account while the exchange rate is not directly targeted, may have a better chance of having favorable effects on both variables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet